Bio-monitoring of metal impact on metallothioneins levels in the gastropod Phorcus turbinatus (Born, 1778) in the northeastern and the eastern coasts of Tunisia. Issue 1 (15th July 2017) - Boulajfene, Wafa; Strogyloudi, Evangelia; Catsiki, Vassiliki-Angelique; El Mlayah, Ammar; Tlig-Zouari, Sabiha
Abstract: This work is an evaluation of metal contamination degree in Phorcus turbinatus and a monitoring of metals impact on metallothioneins functioning. The gastropod was sampled from six stations along the northeastern and eastern coasts of Tunisia during four seasons (2014–2015). Our results suggested that sedimentological metallic contents (Copper, Zinc and Cadmium) vary significantly depending on stations and not significantly according to seasons except for copper. Nevertheless, differences were no significant between stations and significant between seasons as for ambient factors, metallic intrinsic contents and metallothioneins rates. The monodonta tissue seems to be enriched in the four analyzed metals (Cu, Zn, Cd and Hg) and this species seems to have an ability to accumulate metals. Metal effect on the protein induction may be linked to physicochemical factors (temperature, O2 and Cu contents in sediment). In fact, metallothioneins levels were positively correlated to the dissolved oxygen rates and negatively linked to temperature. Highlights: P . turbinatus is provided with an accumulator power of metals. Significant correlation between MTs levels and the three metals Cu, Cd and Hg MTs positively linked to O2 and to Cu rate in sediment and negatively related to T°.